Phytochemical Screening and Total Flavonoid Content of the Combined Ethanol Extract of Turmeric (Curcuma longa) Rhizome and Ginseng (Panax ginseng) Root - Anak Agung Istri Mas Padmiswari; Nadya Treesna Wulansari; Kadek Buja Harditya (Jurnal Pijar MIPA, 2026)
Turmeric (Curcuma longa) and ginseng (Panax ginseng) are medicinal plants with high antioxidant potential due to their rich phytochemical constituents; however, the synergistic effect of their combined extraction has not been fully explored. This study aimed to identify the secondary metabolite profile and determine the total flavonoid content of the combined ethanolic extract of turmeric rhizome and ginseng root at a 1:1 ratio. Extraction was performed using the maceration method with 96% ethanol. Qualitative phytochemical screening was conducted to identify major secondary metabolites, while total flavonoid content was measured using the aluminium chloride (AlCl₃) colourimetric method by UV-Vis spectrophotometry at 415 nm with quercetin as the standard. All measurements were carried out in triplicate and analyzed using One-Way ANOVA followed by Tukey HSD post hoc test. The phytochemical screening showed positive results for flavonoids, saponins, tannins/phenolics, and triterpenoids. The combined extract exhibited a total flavonoid content of 48.65 ± 1.2 mg QE/g extract, which was significantly higher (p < 0.05) than the single turmeric extract (41.05 ± 0.9 mg QE/g) and the single ginseng extract (27.59 ± 0.7 mg QE/g). These findings indicate a synergistic interaction during co-maceration that enhanced flavonoid yield. In conclusion, the combined formulation improved the extraction efficiency of bioactive compounds and provides a scientific basis for the development of standardized phytopharmaceutical raw materials. Further in vivo studies are recommended to evaluate its therapeutic and neuroprotective potential.